PENGEMBANGAN INSTRUMEN PENILAIAN SIKAP PADA PEMBELAJARAN STEM DENGAN MEDIA PERAHU BERTENAGA UAP DI KELAS V SEKOLAH DASAR - Sabillah, Dena Sapna (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2020)
This research is a research study of attitudes assessment instruments on STEM Learning (science, Technology, Engineering, and Mathematics) with steam-powered boat media in the V-class elementary school to support the 2013 curriculum in the face of real-life globalization challenges. This research is backed by several schools that have not developed an attitude assessment instrument on STEM learning. In addition, teachers assess student attitudes without the use of assessment instruments, so that teachers tend to judge the attitudes of students in subjectively. This research aims to develop and describe the design of an attitude assessment instrument that can be implemented in STEM learning. The research phase uses the Educational Design Research (EDR) method. This research presents 2 stages, namely 1) Analysis and Exploration, research in the early phase of the education design to analyze the needs and context of the problems contained in the field; 2) Design and Construction, at this stage done design and product development. The data collection techniques used in this study are literary studies, interviews, document analysis, and expert judgement. The results of this study confirm that the attitude assessment instruments on STEM Learning are needed in the 2013 curriculum to face the challenges of real life globalization. The resulting product is an attitude assessment rubric in STEM learning. The product is validated by several expert teams so that it is deemed worthy to be used as a form of blowing in the implementation of STEM learning in the primary school V class. Â Â